(R)‐α‐trifluoromethylalanine containing short peptide in the inhibition of amyloid peptide fibrillation. Issue 5 (September 2015) - Botz, Alexandra; Gasparik, Vincent; Devillers, Emmanuelle; Hoffmann, Anais R. F.; Caillon, Lucie; Chelain, Evelyne; Lequin, Olivier; Brigaud, Thierry; Khemtemourian, Lucie
ABSTRACT: The extracellular deposition of insoluble amyloid fibrils resulting from the aggregation of the amyloid‐β (Aβ) is a pathological feature of neuronal loss in Alzheimer's disease (AD). Numerous small molecules have been reported to interfere with the process of Aβ aggregation. Compounds containing aromatic structures, hydrophobic amino acids and/or the α‐aminoisobutyric acid (Aib) as β‐sheet breaker elements have been reported to be effective inhibitors of Aβ aggregation. We synthesized two peptides, one containing the Aib amino acid and the other including its trifluoromethylated analog (R)‐α‐Trifluoromethylalanine ((R)‐Tfm‐Alanine) and we evaluated the impact of these peptides on Aβ amyloid formation. The compounds were tested by standard methods such as thioflavin‐T fluorescence spectroscopy and transmission electron microscopy but also by circular dichroism, liquid state nuclear magnetic resonance (NMR) and NMR saturation transfer difference (STD) experiments to further characterize the effect of the two molecules on Aβ structure and on the kinetics of depletion of monomeric, soluble Aβ. Our results demonstrate that the peptide containing Aib reduces the quantity of aggregates containing β‐sheet structure but slightly inhibits Aβ fibril formation, while the molecule including the trifluoromethyl (Tfm) group slows down the kinetics of Aβ fibril formation, delays the random coil to β‐sheet structure transition and induces a change in the oligomerization pathway. These results suggest that the hydrophobic Tfm group has a better affinity with Aβ than the methyl groups of the Aib and that this Tfm group is effective and important in preventing the Aβ aggregation. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 104: 601–610, 2015.